A review of cavity-enhanced Raman spectroscopy as a gas sensing method. Issue 5 (27th May 2020) - Wang, Pinyi; Chen, Weigen; Wan, Fu; Wang, Jianxin; Hu, Jin
Abstract: Raman spectroscopy is a powerful method for gas sensing but is limited by the inherently weak Raman effect. Due to the increase in intracavity laser power or improvement in spontaneous emission, cavity-enhanced technology is a useful enhancement method for the improvement of the limits of detection, which permits Raman spectroscopy to get better applications in gas sensing. In this article, a brief review of several cavity-enhanced technologies used in gas sensing by Raman spectroscopy is presented, the enhanced-cavities including multiple-pass cavities, Fabry–Perot cavities, laser cavities, and microcavities. Finally, the advantages and limitations of these different technologies are discussed.